2007
DOI: 10.1158/1078-0432.ccr-07-0064
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics and Pharmacodynamics of Paclitaxel and Carboplatin in Ovarian Cancer Patients: A Study by the European Organization for Research and Treatment of Cancer-Pharmacology and Molecular Mechanisms Group and New Drug Development Group

Abstract: Purpose: Paclitaxel and carboplatin are frequently used in advanced ovarian cancer following cytoreductive surgery. Threshold models have been used to predict paclitaxel pharmacokineticpharmacodynamics, whereas the time above paclitaxel plasma concentration of 0.05 to 0.2 Amol/L (t C > 0.05-0.2 ) predicts neutropenia.The objective of this study was to build a population pharmacokinetic-pharmacodynamic model of paclitaxel/carboplatin in ovarian cancer patients. Experimental Design: One hundred thirty-nine ovari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 34 publications
7
90
1
Order By: Relevance
“…This can be explained due to missing concentration-time data at the beginning of the paclitaxel infusion. Paclitaxel maximum elimination capacity (VM EL ) and plasma concentration at half VM EL (KM EL ) were lower for the weekly regimen compared to the 3-weekly regimen (14.5 vs 29.6 µmol/h and 0.174 vs 3.12 µmol/L, respectively) [24]. For VM EL , this may be due to the elimination pathway not being saturated to full capacity with the lower weekly dose of paclitaxel.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This can be explained due to missing concentration-time data at the beginning of the paclitaxel infusion. Paclitaxel maximum elimination capacity (VM EL ) and plasma concentration at half VM EL (KM EL ) were lower for the weekly regimen compared to the 3-weekly regimen (14.5 vs 29.6 µmol/h and 0.174 vs 3.12 µmol/L, respectively) [24]. For VM EL , this may be due to the elimination pathway not being saturated to full capacity with the lower weekly dose of paclitaxel.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, the predictive performance of the limited sampling model might be worse, when using real patient data. The strengths of this study include the availability of a population model that had been validated in several patient populations [24,25,30] and the integration of PK and (neuro)-toxicity data into an integrated PK-PD model. Therefore, our findings could result in a clinically relevant reduction of paclitaxel-associated CIPN, further supporting the use of weekly paclitaxel treatment regimens, which usually are preferred by patients and physicians due to its relative ease of administration, convenient monitoring and favorable clinical activity [1-6, 13, 14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(16) Carboplatin used in this regimen has a myelosuppressive effect via the mechanism of DNA-protein damage in bone marrow by means of crosslinking between them, thus resulting in decreased numbers of erythrocytes, leukocytes, and platelets, as well as other toxic effects (neurotoxicity, ototoxicity, and nephrotoxicity). (17,18) It also seems that carboplatin may increase serum TNF-α, suppressing the development of hematologic progenitor cells. (19) Currently, genetic polymorphisms are being investigated to determine their association with paclitaxel-carboplatin hematologic toxicity, depending on race and ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Joerger et al have developed a population pharmacokinetics and pharmacodynamics for the prediction of neutropenia and thrombocytopenia induced by paclitaxel and carboplatin. They have shown that in this group of patients, paclitaxel concentrations greater than 0.05 mmol/L is a good predictive marker for severe neutropenia and clinical outcome, whereas carboplatin exposure is a good predictive marker for thrombocytopenia (Joerger et al 2007a).…”
Section: Modeling and Prediction Of Adverse Eventsmentioning
confidence: 93%